2010
DOI: 10.1172/jci36551
|View full text |Cite
|
Sign up to set email alerts
|

Triggering of TLR7 and TLR8 expressed by human lung cancer cells induces cell survival and chemoresistance

Abstract: Compelling evidence suggests that inflammation, cell survival, and cancer are linked, with a central role played by NF-κB. Recent studies implicate some TLRs in tumor development based on their ability to facilitate tumor growth; however, to our knowledge, involvement of neither TLR7 nor TLR78 has yet been demonstrated. Here we have demonstrated expression of TLR7 and TLR8, the natural receptors for single-stranded RNA, by tumor cells in human lung cancer in situ and in human lung tumor cell lines. Stimulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
178
1
9

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 200 publications
(204 citation statements)
references
References 70 publications
7
178
1
9
Order By: Relevance
“…Previous studies have reported pro-tumorigenic effects for different TLRs, such as TLR2 1418 , TLR4 1923 , TLR5 24 , TLR7 10,11,25 and TLR9 2630 . In prostate and breast cancer, the stimulation of TLR9 induced an over-expression of matrix metalloproteinase 13 as well as an increase of cell invasion 31,32 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported pro-tumorigenic effects for different TLRs, such as TLR2 1418 , TLR4 1923 , TLR5 24 , TLR7 10,11,25 and TLR9 2630 . In prostate and breast cancer, the stimulation of TLR9 induced an over-expression of matrix metalloproteinase 13 as well as an increase of cell invasion 31,32 .…”
Section: Discussionmentioning
confidence: 99%
“…However, in recent years, TLR7 expression by tumor cells has been associated with a pro-tumoral effect in pancreatic adenocarcinoma 25 and in NSCLC 10,11 . We found that stimulation of TLR7 expressed by adenocarcinoma cells modulated the immune infiltrate, leading to a significant expansion in MDSCs, associated with an increased secretion of CCL2 and GM-CSF in the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nous avons étudié par immunohistochimie l'expression de TLR7 et TLR8 sur des coupes de tumeurs provenant de patients opérés de carcinomes pulmonaires non à petites cellules (NSCLC, non-small cell lung carcinoma) [9]. Sur une petite cohorte de 13 patients, nous avons montré que TLR7 est exprimé chez 9 patients, et TLR8 chez les 13 patients, avec des pourcentages d'expression variables allant de moins de 10 % à 100 % de cellules tumorales exprimant TLR7 et/ou TLR8.…”
Section: Expression Des Tlr7 Et Tlr8 Par Les Cellules Tumorales Pulmounclassified
“…Cette activation est dite atypique car IB est phosphorylé 30 min après la stimulation sans être dégradé. La stimulation des cellules tumorales pulmonaires par les ligands de TLR7 ou de TLR8 induit une augmentation de la survie des cellules, en accord avec une augmentation de l'expression de la protéine anti-apoptotique Bcl-2 [9,10].…”
Section: Dernière Heureunclassified